Optic Neuritis Secondary to Paranasal Sinusitis: A Case Report - Khoshsirat, Shahrokh; Majdinasab, Niloofar; Ahangarnazari, Lida (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: Coexistence of optic neuritis (ON) and sinus disorder, particularly the concurrent presentation of both diseases, is a rare and unique condition. In this report, we describe a case of optic neuritis, which was accompanied by posterior ethmoid sinusitis. Case Presentation: Presented with right-sided acute progressive loss of vision in a 61-year-old female due to the direct spread of infection from ethmoid sinus to the optic nerve through dehiscent optic canal. Conclusions: A combination of medical therapy, prior to surgery, with broad spectrum antibiotics and corticosteroids together with right-sided ethmoidectomy and sphenoidectomy led to a complete recovery of vision. She was successfully treated and at follow up of first month, she presented the normal vision acuity.